Identifying with freedom : Indonesia after Suharto - Day, Tony (Critical interventions., 2007)
Indonesia, a huge secular, archipelagic nation-state in Southeast Asia, is one of the world's newest democracies. Yet little is known to outsiders about this complex and fascinating country, the home of the world's largest Muslim community and the scene of recent natural disasters and violent communal struggles. Eleven scholars provide incisive critical appraisals of the leading issues and controversies facing Indonesians as they seek to build a democratic nation that is tolerant of multicultural diversity and free from imperial domination.